Fertilizer Application Method Provides an Environmental-Friendly Nitrogen Management Option for Sugarcane - Quassi de Castro, Sérgio Gustavo; Costa, Vladimir Eliodoro [UNESP]; Quassi de Castro, Saulo Augusto; Carvalho, João Luis Nunes; Borges, Clovis Daniel; de Castro, Rosilaine Araldi; Kölln, Oriel Tiago; Franco, Henrique Coutinho Junqueira (Springer Nature, 2024)
Purpose: Nitrogen fertilizer management is an important agricultural tool that must be optimized to promote sustainable practices since the nitrogen-fertilizer recovery by plants (NRP) is low, leading to nitrogen losses to the environment. In sugarcane, N-fertilization has been investigated over the years but little attention has been given to N-fertilizer application methods. Sugarcane crop production and environmental impact regarding N-fertilizer application methods (i.e., applied onto the sugarcane straw layer and incorporated into the soil) were investigated in the present study aiming to achieve an environmental-friendly cropping system. Methods: Sugarcane yield and NRP, N2O emissions, relevant components of the soil microbiological community and N-fertilizer retention in soil layers were quantified. The experiment was carried out in field conditions where N-fertilizer application methods using 15N-labelled ammonium nitrate (15NH415NO3) were compared to a control treatment with no N-fertilization. Results: Incorporation of N-fertilizer into the soil increased the sugarcane yield by 17% (two-year average) compared to N-fertilizer applied onto the sugarcane straw layer, which was similar to control treatment. There was an increase in NRP-fertilizer of 79% due to the application of N-fertilizer incorporated into the soil. Furthermore, soil incorporation of N-fertilizer decreased N2O emission by 22% with the fertilizer N emission factor reduced four-fold. The N2O emissions were mostly associated with ammonium-oxidizing bacteria (AOB). Conclusions: Our results show that application of N-fertilizer incorporated into the soil is an environmental-friendly N-fertilization management which will improve agricultural sustainability and reduce environmental impacts. Graphical Abstract: (Figure presented.)
Keywords: AOA; AOB; Labelled nitrogen; N2O emission; Nitrogen-fertilizer recovery; Sugarcane yield